Topologically Tunable Conjugated Metal–Organic Frameworks for Modulating Conductivity and Chemiresistive Properties for NH3 Sensing - Shan, Zhen; Xiao, Jian‐Ze; Wu, Miaomiao; Wang, Jinjian; Su, Jian; Yao, Ming‐Shui; Lu, Ming; Wang, Rui; Zhang, Gen (Angewandte Chemie International Edition, 2024)
Electrically conductive metal–organic frameworks (cMOFs) have garnered significant attention in materials science due to their potential applications in modern electrical devices. However, achieving effective modulation of their conductivity has proven to be a major challenge. In this study, we have successfully prepared cMOFs with high conductivity by incorporating electron‐donating fused thiophen rings in the frameworks and extending their π‐conjugated systems through ring‐closing reactions. The conductivity of cMOFs can be precisely modulated ranging from 10−3 to 102 S m−1 by regulating their dimensions and topologies. Furthermore, leveraging the inherent tunable electrical properties based on topology, we successfully demonstrated the potential of these materials as chemiresistive gas sensors with an outstanding response toward 100 ppm NH3 at room temperature. This work not only provides valuable insights into the design of functional cMOFs with different topologies but also enriches the cMOF family with exceptional conductivity properties. Highly conductive metal–organic frameworks (cMOFs) are formed by incorporating electron‐donating fused thiophene rings into their frameworks and extending their π‐conjugated systems. The conductivity can be modulated by adjusting the solvent system, thus regulating the dimensions and topologies of the cMOFs. 1D Cu‐MOF‐1 can be easily processed into thin membranes. The 2D kgm‐Cu‐MOF‐3 has an excellent response toward NH3 at room temperature.